Molecular and biological characterization of a highly pathogenic Trypanosoma cruzi strain isolated from a patient with congenital infection - Gulin, Julián Ernesto Nicolás (2018)
Although many Trypanosoma cruzi (T. cruzi) strains isolated from a wide range of hosts have been characterized, there is a lack of information about biological features from vertically transmitted strains. We describe the molecular and biological characteristics of the T. cruzi VD strain isolated from a congenital Chagas disease patient. The VD strain was typified as DTU TcVI; in vitro sensitivity to nifurtimox (NFX) and beznidazole (BZ) were 2.88 μM and 6.19 μM respectively, while inhibitory concentrations for intracellular amastigotes were 0.24 μM for BZ, and 0.66 μM for NFX. Biological behavior of VD strain was studied in a mouse model of acute infection, resulting in high levels of parasitemia and mortality with a rapid clearence of bloodstream trypomastigotes when treated with BZ or NFX, preventing mortality and reducing parasitic load and intensity of inflammatory infiltrate in skeletal and cardiac muscle. Treatment-induced parasitological cure, evaluated after immunossupression were 41% and 35% for BZ and NFX treatment respectively, suggesting a partial response to these drugs in elimination of parasite burden. This exhaustive characterization of this T. cruzi strain provides the basis for inclusion of this strain in a panel of reference strains for drug screening and adds a new valuable tool for the study of experimental T. cruzi infection.